Women in medieval Europe, 1200-1500 - Ward, Jennifer C. (Routledge, 2016)
Women in Medieval Europe explores the key areas of female experience in the later medieval period, from peasant women to Queens. It considers the women of the later Middle Ages in the context of their social relationships during a time of changing opportunities and activities, so that by 1500 the world of work was becoming increasingly restricted to women. The chapters are arranged thematically to show the varied roles and lives of women in and out of the home, covering topics such as marriage, religion, family and work. For the second edition a new chapter draws together recent work on Jewish and Muslim women, as well as those from other ethnic groups, showing the wide ranging experiences of women from different backgrounds. Particular attention is paid to women at work in the towns, and specifically urban topics such as trade, crafts, healthcare and prostitution. The latest research on women, gender and masculinity has also been incorporated, along with updated further reading recommendations.